Template Synthesis and Characterization of Ni Nanostructures - Gehlawat, Devender; Chauhan, R.P.; Kant, K.; Chakravarti, S.K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
Nanostructures of a typical ferromagnetic material, nickel are fabricated by electro-deposition (in a DC mode) within the pores of polycarbonate track etched membranes. The cylindrical pores with pore diameter 100 nm have been used for present study. Negative template method via two electrode potentiostatic arrangement in electrochemical cell has been used to synthesize the ordered array of one-dimensional Ni nanostructures. Deposition has been carried out at \(41±2\) degree, 1.6 V and so formed one dimensional nanostructure has been obtained at a Copper substrate. The elegant approach of template synthesis has advantage that shape and diameter of one-dimensional nanostructure can be varied as per the requirement, by using the templates of different pore shapes and diameters. Crystalline nature of one-dimensional Ni nanostructures is confirmed by X-ray spectroscopy using Rigaku X-ray diffractometer. I-V characteristics have also been drawn using Keithley source meter, in order to check out the variation in electrical conductivity from bulk to nanoscale.